AFLATOXICOSIS IN EMU (Dromaius novaehollandiae) CHICKS - P.Senthilkumar; T. Lurthu Reetha; P.N. Richard Jagatheesan; J. Selvaraj (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was conducted in the emu chicks reared at Emu Research Unit, Regional Research Centre, Tamil Nadu Veterinary and Animal Sciences University, Pudukkottai during the year 2011. Emu chicks were kept in the brooder with a floor space of 4 sq.ft/chick. Emu chicks were offered emu starter mash from 5th day onwards and water ad libitum. Chicks were showing gradual loss of appetite, lethargy, loss of weight, depression and ruffled feathers from 13th day onwards. Two emu chicks died on subsequent days at the age of 17 and 21 days. Haemorrhage in the subcutis of the thigh region, enlarged liver with mottled and friable in consistency, distended pericardial sac with amber coloured fluid and congested intestinal and tracheal mucous membrane were recorded in the necropsy. Histologically, diffuse severe vacuolar changes of hepatocytes, congestion of e picardium with multifocal mild sub-acute epicarditis and diffuse mild congestion of trachea were observed. The feed sample was analysed for aflatoxin and it c ontained aflatoxin B1 -45ppb and aflatoxin B2 -20ppb. From this study, it can be concluded that aflatoxins in the feed caused death in the emu chicks after 13th and 17th days of feeding.